Effects of Spent and Deoiled Bleaching Earth Filler-Based NPK Fertilization on the Soil Nutrient Status and Growth of Soybean (Glycine max (L. ) Merrill) - Muhammad Parikesit Wisnubroto; Eka Tarwaca Susila Putra; Budiastuti Kurniasih (Universitas Sebelas Maret, 2021)
The bleaching process at the crude palm oil (CPO) refinery stage is one of the processes sufficient to determine the quality of the cooking oil produced. CPO is refined to eliminate the unacceptable substances before consumption. The process produces spent bleaching earth (SBE) and deoiled bleaching earth (DBE) classified as hazardous and toxic material waste. However, according to several studies, SBE and DBE have the potential as filler materials in NPK fertilizers. This study aimed to study the effect of SBE and DBE filler-based NPK fertilization on the soil nutrient status and growth characteristics of soybean, thereby determining if the SBE and DBE materials can be used to replace some of the filler components in the NPK fertilizers. The study was a single factor experiment arranged in a Randomized Complete Block Design (RCBD) consisting of four blocks as replications. The treatments tested were fertilization of 10% bentonite clay mineral filler-based NPK (control), 5% bentonite clay mineral + 5% SBE filler-based NPK and 5% bentonite clay mineral + 5% DBE filler-based NPK. The data were analyzed using ANOVA and tested using LSD test at a 95% confidence level. The results showed that the SBE and DBE materials could partially replace the filler components in bentonite clay filler-based NPK fertilizers, which were shown to have the same effect on soil chemical properties and levels of heavy metals after treatment, levels and uptake of N, P, K, Ca and Mg in plants tissues and growth characteristic in the form of total dry weight.